Tachinid flies (Diptera: Tachinidae) reared from deciduous plant-feeding lepidopteran larvae at Hokkaido University Tomakomai Forest (Japan), with descriptions of three new species - Shima, Hiroshi; Abe, Tomokazu; Libra, Martin (Zootaxa, 2021)
Seven species of tachinid flies reared from herbivorous lepidopterans collected from the deciduous forest canopy at Hokkaido University Tomakomai Experimental Forest (0.2 ha plot), Hokkaido, Japan, are recorded and described: Blepharomyia brevicornis sp. nov. ex Erannis golda Djakonov (Geometridae), Catocala lara Bremer and Orthosia odiosa (Butler) (both Noctuidae); Ctenophorinia grisea Mesnil ex Himeropteryx miraculosa Staudinger (Notodontidae); Blepharipa carbonata (Mesnil) ex Marumba jankowskii (Oberthür) (Sphingidae); Cyzenis equifacialis sp. nov. ex Faristenia geminisignella Ponomarenko (Gelechiidae), Archips crataegana (Hübner), A. nigricauda Walshingham, Epinotia exquisitana Christoph and Pseudohedya gradana Christo (all Tortricidae); Cyzenis tetrasetosa sp. nov. ex Lomographa simplicior (Butler), Operophtera brunnea Nakajima and O. relegata Prout (Geometridae); Eulasiona zimini Mesnil ex Archips crataegana (Hübner), Pseudohedya gradana (Christoph), Rhopobota naevana (Hübner) and Rhopobota sp. (all Tortricidae); Panzeria sp. (nr. japonica Shima) ex Erannis golda Djakonov (Geometridae). The genus Eulasiona Townsend is moved to the subfamily Tachininae from its present position in the subfamily Dexiinae, and the female and puparium of Eulasiona zimini Mesnil are described for the first time. The parasitization rates and life habits of these tachinids are briefly discussed.